Hubungan Pemberian PKMK (Pangan Untuk Keperluan Medis Khusus) Berupa Susu Dengan Pertumbuhan Balita Yang Mengalami Stunting: The Relationship Between Providing PKMK (Food for Special Medical Needs) in the Form of Milk and the Growth of Toddlers Experiencing Stunting - Fachdian (Dohara POAJ, 2025)
Introduction: The devastating impact of stunting that haunts until old age makes this condition very important to prevent. Good nutrition and a healthy body are the keys to preventing stunting. One of the efforts is by providing PKMK (Food for Special Medical Purposes) in the form of milk. Providing additional food or nutritional intake is one of the efforts made by the government. Research Objective To determine the relationship between the provision of PKMK in the form of milk with the growth of toddlers who are stunted. Methods: In this study the authors used Descriptive Research with Retrospective Descriptive. The population in this study were toddlers who were stunted in the Kembangan Hospital Pediatric Clinic starting the PKMK program as many as 67 toddlers. The sample in this study were 67 respondents with the total sample technique. Data collection tools in this study were using observation sheets and weight measurement tools with digital weighing devices and measuring height with measuring tape. Researchers used the chi-square test. .Results: The results of the statistical test results obtained p-value = 0,000 means p-value < α (0,05). Discussion: There is a relationship between the provision of CHPM in the form of milk with the growth of toddlers who experience stunting.